Study of aluminothermic slag leaching for uranium and thorium recovery - VANDERLEI VILAÇA MOURA; Talita Santos; Claubia Pereira (Brazilian Journal of Radiation Sciences, 2022)
The need for energy by modern society is increasing. On the other hand, it is necessary to reduce costs and environmental impact. In this perspective, the recovery of uranium present in industrial waste from the processing of naturally occurring radioactive material (NORM) appears as a possible complement to the mining stage of the Nuclear Fuel Cycle. NORM's uranium recovery can reduce environmental liabilities and mineral processing costs (especially blasting, crushing, and grinding). The industrial residue of this study, a type of aluminothermic slag, comes from the metallurgical processing of columbite (niobium and tantalum mineral) and has a content, measured by X-ray fluorescence, of 1.78% of U3O8. This content is higher, for example than those found in Lagoa Real-BA (0.2% in rock) and Santa Quitéria-CE (0.1% in rock). Another material that will be studied is ThO2, which is also present in the slag with a content, measured by X-ray fluorescence, around 3.66%. The process parameters analyzed were pH of the solution, time, granulometry and percentage of solids. The metallurgical recovery of U3O8 reached a maximum value of 71,3% with pH = 1, time of 8 hours, 65 % percentage of solids, and 200 µm of granulometry. The metallurgical recovery of ThO2 reached a maximum value of 69,7% with pH = 1, time of 8 hours, 65 % percentage of solids, and 200 µm of granulometry.